Nursing Diagnoses in People with Diabetes Mellitus After Participation in an Educational Program - Lilian Cristiane Gomes; Autran José da Silva Júnior (Galenos Publishing House, 2022)
Objective:To identify the nursing diagnoses in people with diabetes mellitus who participated in an educational program about the disease.Method:This is an explo rator y-des cript ive research, with a quantitative approach, through the study of multiple cases, in a sample of 18 people with type 2 diabetes mellitus. In the form of an individual interview, each participant responded to the data collection instruments, before the beginning and after the end of the program, in addition to having their feet and shoes evaluated and their weight and height were measured to calculate the body mass index, as well as the capillary blood glucose. For the identification of nursing diagnoses, data from the final assessment were considered.Results:Twelve nursing diagnoses and five domains were identified, with a variation between two and nine diagnoses per participant and a mean of 5.4. The health promotion diagnoses and the nutrition and safety/protection domains stand out.Conclusion:The identification of care needs, through the nursing diagnoses, will allow the search for new strategies for the design of other educational and clinical monitoring programs, in order to maintain and/or maximize motivation and engagement in healthy behaviors, with a view to effective diabetes mellitus control and improving quality of life.